Cover Image. (10th March 2020) - Roth, Michael E.; Unger, Joseph M.; O'Mara, Ann M.; Lewis, Mark A.; Budd, Troy; Johnson, Rebecca H.; Pollock, Brad H.; Blanke, Charles; Freyer, David R.
Abstract : The cover image is based on the Original Research Enrollment of adolescents and young adults onto SWOG cancer research network clinical trials: A comparative analysis by treatment site and era by Michael E. Roth et al., https://doi.org/10.1002/cam4.2891 . Cover image © Wiley Images.